Exploring alternative assessments during COVID: Instructor experiences using oral exams - Gaines, Theresa; Burrows, Nikita Lauren (Frontiers in Education, 2024)
Research into conventional summative assessment methods, such as written exams, has been extensively documented in the literature. However, as academia evolves in response to changing dynamics, there is a growing demand for more robust summative assessment approaches. Oral exams have emerged as a noteworthy form of summative assessment with intrinsic formative qualities, enabling instructors to delve deeply into students' comprehension within a meaningful learning framework. Considering the constraints imposed by the traditional written examination format during the COVID pandemic, two educators implemented oral assessments in their chemistry courses, one in general chemistry and the other in organic chemistry. This article presents a comprehensive account of their approach, course structure, rubrics, documentation procedures, and the challenges associated with implementing oral exams. Furthermore, the authors offer insights derived from perceived course outcomes, experiences, collaborative efforts, and reflections from this transformative process. Through candid exploration, this article delves into both the potential advantages and the hurdles associated with the adoption of oral exams in chemistry education. It serves as a valuable resource for educators seeking innovative assessment strategies.